ZnT35C Maintains Zinc Homeostasis to Regulate Spermatogenesis in Drosophila Testis. - He, J.; Fang, Y.; Zhao, L.; Su, Y. (Archives of Insect Biochemistry and Physiology, 2025)
Zinc homeostasis contributes significantly to numerous physiological processes. Drosophila ZnT35C protein, a zinc transporter encoded by CG3994, is chiefly located on the cell membrane and facilitates the transport of zinc from the cytoplasm to the extracellular space to sustain zinc homeostasis within the organism. Previous studies about ZnT35C have involved diverse structures such as the Malpighian tubules, adult brain, and sensory nervous system. Nonetheless, the role of ZnT35C in Drosophila spermatogenesis remained unclear. In our study, we discovered that ZnT35C plays a pivotal role in Drosophila spermatogenesis. Its knockdown resulted in sperm loss and male infertility. When ZnT35C was knocked down in cyst cells, zinc was concentrated within cyst cells, inhibiting the proper development of germ cells and thereby causing the incapacity of flies to generate mature sperms. Zinc supplementation can effectively rescue this failure of spermatogenesis. Our research outcomes suggest that ZnT35C, through modulating the zinc environment within the testes, impacts the male fertility of Drosophila, occupying a crucial position in the spermatogenesis process.